Reactions of N,3-diarylpropiolamides with arenes under superelectrophilic activation: synthesis of 4,4-diaryl-3,4-dihydroquinolin-2(1H)-ones and their derivatives - Gurskaya, Larisa Yu.; Belyanskaya, Diana S.; Ryabukhin, Dmitry S.; Nilov, Denis I.; Boyarskaya, Irina A.; Vasilyev, Aleksander V. (Beilstein Journal of Organic Chemistry, 2016)
The reaction of 3-aryl-N-(aryl)propiolamides with arenes in TfOH at room temperature for 0.5 h led to 4,4-diaryl-3,4-dihydroquinolin-2-(1H)-ones in yields of 44–98%. The obtained dihydroquinolinones were further transformed into the corresponding N-acyl or N-formyl derivatives. For the latter, the superelectrophilic activation of the N-formyl group by TfOH in the reaction with benzene resulted in the formation of N-(diphenylmethyl)-substituted dihydroquinolinones.
Keywords: alkynes; quinolinones; Friedel–Crafts reactions; superacids; superelectrophilic activation